PENGEMBANGAN MODEL PEMBINAAN KOMPETENSI CALON GURU MATEMATIKA MELALUI LESSON STUDY - Anwar, Rahmad Bustanul; Rahmawati, Dwi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2014)
Education has a very important role in improving the quality of human resources. Therefore, education is expected to be one of the ways to prepare generations of qualified human resources and has the ability to deal with the progress of time and technology development . In order to enhance the quality of student mastery of competencies in the development of prospective teachers in this study will be applied to the activities in the process of lesson study in lecture . Lesson study is a model of coaching to people who work as both teacher educators and lecturers through collaborative learning and assessment in building sustainable learning communities. The purpose of this research is to improve the competence of prospective mathematics teachers through lesson study . More specifically , this study aims to describe the efforts made to improve the pedagogical, professional competence , social competence and personal competence prospective mathematics teachers through lesson study . Subjects in this study were students who took the micro teaching courses totaling 15 students , divided into 3 group . This type of research is a qualitative descriptive study is to develop the competence of prospective mathematics teachers through lesson study . Lesson study conducted collaborated with Action Research activities ( Action Reseach). The results of this research activity is the implementation of lesson study to greater competence to prospective teachers teaching mathematics through the micro subjects namely: pedagogical competence categories were 80 % and 20 % lower, professional competence categories were 46.7 % and 53.3 % lower, personal competence 100 % category being and social competence categories were 86.7 % and 13.3 % lower .